Lacunary equi-statistical convergence of positive linear operators - Aktuglu, Hueseyin; Gezer, Halil (Versita, 2009)
In this paper, the concept of lacunary equi-statistical convergence is introduced and it is shown that lacunary equi-statistical convergence lies between lacunary statistical pointwise and lacunary statistical uniform convergence. Inclusion relations between equi-statistical and lacunary equi-statistical convergence are investigated and it is proved that, under some conditions, lacunary equi-statistical convergence and equi-statistical convergence are equivalent to each other. A Korovkin type approximation theorem via lacunary equi-statistical convergence is proved. Moreover it is shown that our Korovkin type approximation theorem is a non-trivial extension of some well-known Korovkin type approximation theorems. Finally the rates of lacunary equi-statistical convergence by the help of modulus of continuity of positive linear operators are studied.
Keywords: Statistical convergence; Lacunary statistical convergence; A-statistical convergence; Equi-statistical convergence; Korovkin type approximation theorem; Order of convergence